Socio-economic Development in the Arid Region of Rajasthan - Mehta, B C (Annals of Arid Zone, 2016)
The level of socio-economic development and the incidence of poverty was studied for the arid districts of Rajasthan. Poverty was measured by using the head-count ratio, poverty-gap and the Lorenz ratio of the distribution of income. In the western region, 43.34 per cent of the rural population lives under the poverty line and the poverty gap is 29.16 per cent of the required level. Bottom 25 per cent cultivators have only 59 per cent of total rural assets but 23 per cent of total liabilities. Most of the debt incurred is for meeting out household deficit. For the study at district level, composite indicators of Quality of life, agricultural development,agrarian relations,agricultural infrastructure, input use and industrial development were computed fer 1970-71 and 1980-1981. Infrastructural development is low, agrarian relations are pre-capitalist and industrial development is slow. The situation does not seem to have significantly improved during 1971-1981.